2021
DOI: 10.1038/s41598-021-00045-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered protein O-GlcNAcylation in placentas from mothers with diabetes causes aberrant endocytosis in placental trophoblast cells

Abstract: Women with pre-existing diabetes have an increased risk of poor pregnancy outcomes, including disordered fetal growth, caused by changes to placental function. Here we investigate the possibility that the hexosamine biosynthetic pathway, which utilises cellular nutrients to regulate protein function via post-translationally modification with O-linked N-acetylglucosamine (GlcNAc), mediates the placental response to the maternal metabolic milieu. Mass spectrometry analysis revealed that the placental O-GlcNAcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…To better understand the importance of O -GlcNAc in placental tissue, a recent study documented approximately 750 O -GlcNAcylated proteins in trophoblast and fetal capillaries within the villous of the human placenta ( 32 ). Here, we show structural alterations of the placenta in SHR at 14, 17, and 20 DOP.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the importance of O -GlcNAc in placental tissue, a recent study documented approximately 750 O -GlcNAcylated proteins in trophoblast and fetal capillaries within the villous of the human placenta ( 32 ). Here, we show structural alterations of the placenta in SHR at 14, 17, and 20 DOP.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, serine plays an important role in nucleotide synthesis, methylation reactions, and glutathione synthesis 12,14 . The blocking or abnormality of these pathways may impair decidualization and implantation, interfere with trophoblastic function, and affect embryonic growth and development 15,16 …”
Section: A Brief Overview Of Glycolysismentioning
confidence: 99%
“…Clathrin light chain B (LCB) is O-GlcNAcylated in its C-terminal region, at S217/S221 [98], while Clathrin heavy chain 1 (CHC1) is O-GlcNAcylated at S97 which is located within a clathrin box motif (CMB) involved in AP2 binding [99] (Table 2). However, to date, the functional relevance of O-GlcNAc PTM on clathrin chains is fully unknown.…”
Section: O-glcnacylation Of Clathrin and Endocytic Accessory Proteinsmentioning
confidence: 99%
“…Palin and colleagues explored the O-GlcNAcome of placentas from diabetic mothers. They showed that many proteins involved in CME, such as CHC, AP2A2, and Dyn2 are abnormally O-GlcNAcylated in diabetic tissue compared to the control groups [98]. Thus, in addition to phosphorylation-dependent signaling pathways that are crucial to adapt the endocytosis rate to the nutrient uptake and metabolic status of the cell [20], a role for the nutrient-sensing O-GlcNAc modification in the regulation of clathrin-dependent endocytic traffic has emerged.…”
Section: O-glcnacylation Of Clathrin and Endocytic Accessory Proteinsmentioning
confidence: 99%
See 1 more Smart Citation